Effect of n-Alkyl Side Chain Length on the Thermal and Rheological Properties of PolyN-(3-(alkylamino)-N-(3-(isopropylamino)-3-oxopropyl)acrylamide) Homopolymers - Kumari A.; Vishwakarma S.; Mitra K.; Chen C.; Cui S.; Maiti B.; Mondal S.; Biswas C.S.; Maiti P.; Stadler F.J.; Ray B. (My University, 2025)
Four new N-isopropylacrylamide- and N-n-alkyl amine-based acrylamide monomers, N-(3-(alkylamino)-N-(3-(isopropylamino)-3-oxopropyl) acrylamide (Mn) (n = 4, 8, 10, 12) are successfully synthesized and polymerized via reversible addition-fragmentation chain-transfer polymerization (polyMn, n = 4, 8, 10, and 12), which are characterized by gel permeation chromatography, 1H NMR, Fourier transform infra red spectroscopy, thermo-gravimetry-differential thermal analysis, differential scanning calorimetry (DSC), and rheology. All polymers are thermally stable and undergo a two-step degradation process at ≈280 and ≈375 °C. Glass transition temperature (Tg)s of these polymers decrease gradually from 99.6 to 52.5 °C with increasing n-alkyl side chain length. The rheology of these polymers in melt state agrees to a typical Rouse-melt behavior and allows for confirming the Tg determined from DSC. Benzyl alcohol solution rheology proves a weak structural build-up, in particular for polyM12. Comparison of the quantum chemical calculations of polyMns with n = 4–8 reveals increase in backbone helicity with increasing n-alkyl side chain length. © 2021 Wiley-VCH GmbH.